Bones and Brexit: The Past and the Future Introduction to PIA Volume 26/27 - Clare Lewis; Elizabeth Farebrother; Mariana Nabais; Chloe Ward (Papers from the Institute of Archaeology, 2017)
On behalf of the editorial team we are delighted to introduce volumes 26 & 27 of Papers from the Institute of Archaeology. The contributions in this joint volume were intentionally edited together to encompass the diverse range of research undertaken at UCL Institute of Archaeology. The context to this research environment is provided in the forum covering archaeological and heritage sector implications of Britain’s vote in 2016 to leave the European Union. We also introduce three new projects in this joint volume as a new dynamic to Papers from the Institute of Archaeology. The interview has an audio recording accessible in the online version, the winning poster from our poster competition accompanies this editorial, and the first of a series of ‘Postcards from Qatar’ is also presented.
Keywords: Zooarchaeology; Nationalism; UCL Institute of Archaeology; Museum Studies; Brexit; Heritage; Archaeological Science; Archaeology